2012
DOI: 10.1128/jb.00991-12
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence of Staphylococcus hominis, an Opportunistic Pathogen

Abstract: Staphylococcus hominis is a commensal coagulase-negative species of staphylococci. It has been considered a presumptive and opportunistic pathogen that causes nosocomial infections in humans. Here we present the draft genome sequence of S. hominis ZBW5, a multidrug-resistant strain isolated from a human skin sample, which provides opportunities to understand the mechanism and genetic basis of its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…The most numerous species in the analyzed material was S. hominis (18%), which is usually isolated from human skin armpits, arms, legs and trunk. S. hominis usually does not cause serious infections in humans, but it is an opportunistic pathogen that can contribute to infections of hospitalized patients weakened by long-term pharmacological treatment (Jiang et al 2012 ). On the other hand, studies conducted by Pastuszka et al ( 2000 ) in flats of Upper Silesia (Poland) showed that the main bacterial species isolated from indoor air was S. epidermidis , which was present in 76% of studied flats constituting 14% of the total amount of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The most numerous species in the analyzed material was S. hominis (18%), which is usually isolated from human skin armpits, arms, legs and trunk. S. hominis usually does not cause serious infections in humans, but it is an opportunistic pathogen that can contribute to infections of hospitalized patients weakened by long-term pharmacological treatment (Jiang et al 2012 ). On the other hand, studies conducted by Pastuszka et al ( 2000 ) in flats of Upper Silesia (Poland) showed that the main bacterial species isolated from indoor air was S. epidermidis , which was present in 76% of studied flats constituting 14% of the total amount of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…All the pure cultures were frozen at -80°C and shipped to our laboratory for definite identification and further analysis. The identities of all isolates were ratified using Matrix-assisted laser desorption ionisation-time of flight mass spectrometry (MALDI-TOF) as described previously [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The genome contains 58 tRNA genes coding for all amino acids and 2,248 predicted protein-coding genes, consistent with other staphylococci (3,5). We identified numerous putative virulence factors.…”
mentioning
confidence: 83%